2000
DOI: 10.1089/mdr.2000.6.259
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolones Inhibit PreferentiallyStreptococcus pneumoniaeDNA Topoisomerase IV Than DNA Gyrase Native Proteins

Abstract: The genes encoding the subunits of DNA topoisomerase IV (parC and parE) and DNA gyrase (gyrA and gyrB) of Streptococcus pneumoniae were cloned and overproduced in Escherichia coli by using the T7promoter-T7 RNA polymerase system. The four subunits were separately purified to near homogeneity by column chromatography. Protein purification was achieved by DEAE-sepharose, heparin-agarose, and hydroxylapatite chromatography. DNA topoisomerase IV was reconstituted when ParC and ParE were combined at a 3.8-fold exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
21
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Under these conditions the WT and H103Y mutant ParE had identical specific activities either in the decatenation assay (3 ϫ 10 5 U/mg) or in the relaxation assay (4 ϫ 10 4 U/mg). These activities were within the range reported for the WT topoisomerase IV of S. pneumoniae (5,20) and, as described previously, the relaxation activity was even about 11-fold lower than the decatenation activity for the ParE mutant topoisomerase IV (8,11,20). Since the specific topoisomerase IV activities of the homologs containing WT ParE and H103Y mutant ParE were determined in the presence of an excess of ATP, this could have hidden more-subtle alterations in ATP binding.…”
supporting
confidence: 90%
“…Under these conditions the WT and H103Y mutant ParE had identical specific activities either in the decatenation assay (3 ϫ 10 5 U/mg) or in the relaxation assay (4 ϫ 10 4 U/mg). These activities were within the range reported for the WT topoisomerase IV of S. pneumoniae (5,20) and, as described previously, the relaxation activity was even about 11-fold lower than the decatenation activity for the ParE mutant topoisomerase IV (8,11,20). Since the specific topoisomerase IV activities of the homologs containing WT ParE and H103Y mutant ParE were determined in the presence of an excess of ATP, this could have hidden more-subtle alterations in ATP binding.…”
supporting
confidence: 90%
“…The drug concentrations causing 50% inhibition of kinetoplast DNA decatenation by topoisomerase IV were 10 to 20 M for both drugs (data not shown). Other studies have reported similar findings (4,14,17,22). In DNA cleavage assays for gyrase and topoisomerase IV, both drugs caused 25% linearization of input DNA at 80 and 2.5 M, respectively.…”
supporting
confidence: 73%
“…Despite the functional similarities between topoisomerase IV (topo IV) and gyrase, their susceptibility to FQs varies across bacterial species (14). In S. pneumoniae, the primary target for LVX is topo IV (15)(16)(17)(18), while gyrase is the primary target for moxifloxacin (19). Type II topoisomerases maintain DNA topology and solve the topological problems associated with DNA replication, transcription, and recombination (20).…”
mentioning
confidence: 99%